Localization in multiple-input multiple-output systems based on passive repeaters - Eissa, Mahmoud (Progress in electromagnetics research C)
This paper presents a novel localization method based on the implementation of passive repeaters in multiple-input multiple-output (MIMO) systems. Passive repeaters can help in localizing users by taking advantage of their spreading in the communication environments. In the proposed method, the target area is divided into a grid. Each location in this grid has a unique eld interference created by repeaters. Because of the unique eld interference, each location causes a unique eld signature at the base station when a user in that location transmits signals. The eld signature corresponding to the center of each grid cell is used as a ngerprint for localizing users in that cell, and for all cells, a bank of matched lters corresponding to all stored ngerprints is constructed. When a signal arrives at the base station, the generated eld signature is correlated with the bank of matched lters, and the location is determined based on the maximum correlation value. The numerical analysis is performed to verify the validity of the proposed method, and it is found that by means of passive repeaters, the user location can be determined with no need of calculating additional parameters.